The Implementation of Land Provision for Development for The Public Interest in Merauke Land Papua Province - et al., Al Sentot Sudarwanto (International Journal of Advanced Science and Technology, 2019)
This research is intended to find out the problems happening in the process of land provision for the public interest and the solutions that can be given to overcome the problem happening. This is a law research with specification as an emphirical law research, e. g. the research using emphirical facts. The data resources used are the primary data and secondary ones. The data analysis used is qualitative by using interactive technique. The Implementation of Land Provision for the Public Interest in Merauke Land, Papua Province, besides referring to the Law Regulation of the Central Government, it still refers to the Regional Regulation which has a specific autonomy characteristics and considers the local wisdom by doing some approaches and deliberations to the custom society institution. The invisible area borders of custom land ownership that causes new problems when it will be done the land liberation for the public interests, the non-existence of the land price standarization that causes difficulties in giving detriment substitution, and the absence of a regulation and a specific map related to the custom land ownership of original society of Merauke, are the factors impeding the land provision for the public interest in Merauke Regency, Papua Province. The Government of Merauke Regency, in land provisioning for the public interest, should carry out socializations to the owner of land territory right and deliberations in its process.